The RD114/simian type D retrovirus receptor is a neutral amino acid transporter - Rasko, John E. J. (The National Academy of Sciences, 1999)
The RD114/simian type D retroviruses, which include the feline endogenous retrovirus RD114, all strains of simian immunosuppressive type D retroviruses, the avian reticuloendotheliosis group including spleen necrosis virus, and baboon endogenous virus, use a common cell-surface receptor for cell entry. We have used a retroviral cDNA library approach, involving transfer and expression of cDNAs from highly infectable HeLa cells to nonpermissive NIH 3T3 mouse cells, to clone and identify this receptor. The cloned cDNA, denoted RDR, is an allele of the previously cloned neutral amino acid transporter ATB(0) (SLC1A5). Both RDR and ATB(0) serve as retrovirus receptors and both show specific transport of neutral amino acids. We have localized the receptor by radiation hybrid mapping to a region of about 500-kb pairs on the long arm of human chromosome 19 at q13.3. Infection of cells with RD114/type D retroviruses results in impaired amino acid transport, suggesting a mechanism for virus toxicity and immunosuppression. The identification and functional characterization of this retrovirus receptor provide insight into the retrovirus life cycle and pathogenesis and will be an important tool for optimization of gene therapy using vectors derived from RD114/type D retroviruses.